The Role of Academic Self-Efficacy and Mindset on Academic Grit among Civil Engineering Students - Purwani, Galuh Ridha; Muarifah, Alif; Wahyuni, Indah Fajar (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2025)
This research aimed to empirically examine the role of academic self-efficacy and mindset on grit in civil engineering students. Grit is the persistence required by students in academic field to complete school, specifically at the stage of final project. A quantitative method was used with a correlational design to analyze 335 final year students of civil engineering program selected through proportional random sampling. Data analysis was carried out using Structural Equation Modeling-Partial Least Squares (SEM-PLS) method. The results showed that academic mindset and self-efficacy had a significant effect on grit with a contribution of 26.2%, while the remaining 73.8% was influenced by other factors. This research reported the importance of psychological factors, such as mindset and self-efficacy, in increasing' persistence to compete long-term academic tasks.